Resident Memory B Cells in Barrier Tissues - Lee, Choong Man; Oh, Ji Eun (Frontiers in Immunology, 2022)
Epithelial barriers, which include the gastrointestinal, respiratory, and genitourinary mucosa, compose the body’s front line of defense. Since barrier tissues are persistently exposed to microbial challenges, a rapid response that can deal with diverse invading pathogens is crucial. Because B cells have been perceived as indirectly contributing to immune responses through antibody production, B cells functioning in the peripheral organs have been outside the scope of researchers. However, recent evidence supports the existence of tissue-resident memory B cells (BRMs) in the lungs. This population’s defensive response was stronger and faster than that of their circulating counterparts and could resist heterogeneous strains. With such traits, BRMs could be a promising target for vaccine design, but much about them remains to be revealed, including their locations, origin, specific markers, and the mechanisms of their establishment and maintenance. There is evidence for resident B cells in organs other than the lungs, suggesting that B cells are directly involved in the immune reactions of multiple non-lymphoid organs. This review summarizes the history of the discovery of BRMs and discusses important unresolved questions. Unique characteristics of humoral immunity that play an important role in the peripheral organs will be described briefly. Future research on B cells residing in non-lymphoid organs will provide new insights to help solve major problems regarding human health.